UZBEK GAS FOR EXPORT: WILL POLITICAL MANEUVERING BETWEEN CHINA AND RUSSIA RESULT IN HIGHER EXPORT PRICE? - KAKHAROV, Jahangir (CENTRAL ASIA AND THE CAUCASUS, 2008)
The main research question is “Will political maneuvering between China and Russia result in higher export price for Uzbek gas?” This is especially peculiar given the fact that many analysts consider the price that Russia pays for Uzbek gas to be lower than a fair market price. Currently, the price of gas exports from Uzbekistan is 160 per 1,000 cu m. On the other hand, Gazprom charges its European customers an average of 350 per 1,000 cu m. On 1 July, 2008, Uzbekistan and Kazakhstan has begun laying their respective stretches of the Turkmenistan-China gas pipeline. The construction began at the settlement of Saet in the Bukhara region. The cost of the Uzbek stretch of the gas pipeline is estimated to be over 2 billion. The total cost of the 1,818-kilometer long gas pipeline Turkmenistan-China is about 7 billion. If implemented, the Turkmenistan-China pipeline might undermine Russia’s ability to manipulate the Central Asian gas market and stir up energy competition between Russia and China. Some analysts argue that this would presumably secure higher profits for Uzbekistan, as well as give it a greater degree of political freedom. It should be noted that with estimated natural gas reserves of 66.2 trillion cubic feet (Tcf), Uzbekistan is the third largest natural gas producer in the Commonwealth of Independent States (after Russia and Turkmenistan) and one of the top fifteen natural gas producing countries in the world.